2012
DOI: 10.1073/pnas.1116011109
|View full text |Cite
|
Sign up to set email alerts
|

Targeted deletion of thioesterase superfamily member 1 promotes energy expenditure and protects against obesity and insulin resistance

Abstract: Mammalian acyl-CoA thioesterases (Acots) catalyze the hydrolysis of fatty acyl-CoAs to form free fatty acids plus CoA, but their metabolic functions remain undefined. Thioesterase superfamily member 1 (Them1; synonyms Acot11, StarD14, and brown fat inducible thioesterase) is a long-chain fatty acyl-CoA thioesterase that is highly expressed in brown adipose tissue and is regulated by both ambient temperature and food consumption. Here we show that Them1 −/− mice were resistant to diet-induced obesity despite gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
113
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(119 citation statements)
references
References 34 publications
5
113
1
Order By: Relevance
“…The level of free fatty acids is significantly altered in brown adipose tissue and liver in ACOT11 and ACOT13 knockout mice, respectively (30,31). However, in the present study, ACOT11 and ACOT13 knockdown did not affect the level of total amount of free fatty acid in CL1-0 cells.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…The level of free fatty acids is significantly altered in brown adipose tissue and liver in ACOT11 and ACOT13 knockout mice, respectively (30,31). However, in the present study, ACOT11 and ACOT13 knockdown did not affect the level of total amount of free fatty acid in CL1-0 cells.…”
Section: Discussioncontrasting
confidence: 53%
“…Although a previous study suggested that the START domain may be an important regulatory element for ACOT11 (29), the exact mechanisms underlying the regulation and function of ACOT11 remain unknown in lung adenocarcinoma and other tissues. ACOT11 knockout mice revealed increased energy consumption and resistance to high fat diet-induced obesity compared with control mice (30). In addition, loss of ACOT11 leads to resistance to obesity-induced inflammation and endoplasmic reticulum stress (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Adams et al (1) demonstrated that Bfit/Acot11 is induced by cold, and higher gene expression is observed in obesity-resistant strains. However, Acot11 knockout protects against obesity and promotes energy expenditure (42). This study suggested that Acot11 decreases energy expenditure and conserves energy.…”
Section: Discussionmentioning
confidence: 93%
“…However, recent gene-knockout studies on a subgroup of ACOTs revealed that they profoundly affect lipid homeostasis in association with fatty liver development, obesity, and insulin resistance. [5][6][7] Of the ACOT family members, ACOT1 (cytosolic), ACOT2 (mitochondrial), and ACOT7 (cytosolic) have been well characterized for their enzymatic properties (see refs. 1 and 3 for a review).…”
mentioning
confidence: 99%